Pengaruh Preferensi Klien dan Pengalaman Audit Terhadap Pertimbangan Auditor - TRI RAMARAYA KOROY (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to examine how auditors respond in their audit judgment to the client position or preferences. It hypothesized that auditor respond in different ways based on their audit experience. Inexperienced auditors tend to be conservative and more likely to propose audit adjustment than experienced auditors. Experimental study was conducted to 64 auditors from Big 4 and non Big 4 accounting firm. Audit cases used in this study involve an acquisition case to a target division that has the inventory obsolescence problems. Participants asked to make audit judgments i.e. to propose audit adjustment in inventory write-down.Results show that the hypotheses supported and audit experienced play important role in information processing and audit judgment resulted. On average, the client positions have no effect on auditor judgments.